Legal Liability Framework of a Bankrupt Guarantor (Corporate Guarantee) Toward Creditors in Credit Agreements with Debtors : Analysis of Decision No. 318/Pdt.Sus-PKPU/2022 from the Jakarta Commercial Court - Mohammad Rizky Siregar; Muthia Sakti; Iwan Erar Joesoef (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This research examines the legal responsibility of corporate guarantors declared bankrupt for their obligations to creditors in loan agreements, analyzing Court Decision No. 318/Pdt.Sus-PKPU/2022/PN Commercial Court Jakarta Central. The study addresses the legal complexities arising when a corporate guarantee becomes insolvent before the principal debtor defaults, creating jurisdictional conflicts between bankruptcy law and guarantee obligations. Using normative legal research methodology with a juridical normative approach, this study analyzes the application of Article 229(2) in conjunction with Article 278(6) of Law No. 37/2004 on Bankruptcy and Suspension of Debt Payment Obligations (K-PKPU) and Article 1381 of the Civil Code. The research reveals that the curator's action in obstructing and rejecting PT KawanCicil Teknologi Utama's claim registration against the bankrupt guarantor without proper judicial determination constitutes conduct not based on applicable laws and regulations. The findings demonstrate that when a guarantor is declared bankrupt and the debtor is in default, the Supervisory Judge and Curator must accept PT KawanCicil Teknologi Utama as a creditor with rights to the debtor's assets during asset liquidation proceedings. The study concludes that bankruptcy declaration of a guarantor does not automatically terminate guarantee obligations under Article 1381 of the Civil Code, as bankruptcy is not enumerated among the causes of contract termination. This research contributes to legal certainty in corporate guarantee enforcement within Indonesia's bankruptcy framework and provides recommendations for legislative harmonization between conflicting provisions in bankruptcy law.